THE EFFECT OF RESTAURANT TAX RATES PERCEPTION AND FINANCIAL CONDITION OF FIA UI STUDENTS ON FOOD AND BEVERAGE CONSUMPTION BEHAVIOR IN RESTAURANTS IN JAKARTA - Arumi Firja; chrisel valery; Deborah Feodora; Isabel Manuela; Vanesia Aurora (Universitas Tulungagung, 2025)
The growth of restaurants in Jakarta and the implementation of Restaurant Tax highlight the need to understand how students respond to tax-related price components in their consumption behavior. This study examines the influence of Restaurant Tax Rate Perception and Financial Condition on Food and Beverage Consumption Behavior among 96 FIA UI students using a quantitative approach and multiple linear regression. The results show that tax perception has a positive but insignificant effect, indicating that the tax is viewed as a normal component of final prices and does not meaningfully affect consumption decisions. Financial condition shows a positive and significant effect in the initial model, but becomes insignificant after control variables are added. Simultaneously, both variables significantly influence consumption behavior, with an Adjusted R-Square of 24%–29%, suggesting that students’ consumption patterns are also shaped by other factors such as preferences, habits, and social influences.